PENGARUH PEMBERIAN COOKIES DENGAN PENAMBAHAN TEPUNG TEMPE DAN KACANG MERAH TERHADAP PENINGKATAN BERAT BADAN BALITA GIZI KURANG - Aprilia Aprilia; Sartono Sartono; Afriyana Siregar (JURNAL MEDIA KESEHATAN, 2023)
The problem of malnutrition in toddlers is still quite high, based on the results of SSGI 2021, the problem of malnutrition in Indonesia for the age group 0-59 months is 17%, while the prevalence of undernourished toddlers in South Sumatra is 15.7% and for the prevalence of undernourished toddlers less in the city of Palembang by 16.1%. The study aimed to find out the effect of giving tempeh and red bean cookies on the increase in undernourished toddlers' weight in the Working Area of ​​the Taman Bacaan Palembang Health Center. Methods of research is a Quasi Experiment with a pretest-posttest control group design. The statistical tests used were the t-dependent test and the independent t-test which were analyzed by univariate and bivariate. The results showed The average sample weight before the intervention in the treatment group was 8.88 kg to 9.33 kg after the intervention. Whereas in the comparison group, the weight before the intervention was 9.66 kg to 9.95 kg after the intervention. The results of the statistical test (t-independent) obtained a p-value of 0.006 so it can be concluded that there was an effect of giving tempeh and red bean cookies on weight changes for undernourished toddlers in the working area of ​​the Taman Bacaan Palembang Health Center. From the results of the study, it was suggested to parents of toddlers to continue consuming high-calorie foods such as formula cookies, tempeh flour, and red beans so that they can gradually increase their toddler's weight. Keywords: malnutrition, body weight, cookies with the addition of tempe flour and red beans